The ifo Human Resources Survey - Daria Schaller; Jonas Hennrich; Klaus Wohlrabe (CESifo GmbH, 2025)
This paper documents the methodology, content, and evolution of the ifo Human Resources (HR) Survey, a quarterly survey conducted by the ifo Institute since 2008 that targets human resource managers in German firms. While the ifo Institute's traditional business surveys capture general management perspectives, the ifo HR Survey fills a crucial gap by focusing on personnel management strategies, recruitment practices, and workforce development. The survey consists of regular questions about personnel flexibilization instruments, on the company, or about further training measures complemented by special modules addressing current policy issues and labor market challenges. The paper describes the survey's panel composition with currently about 900 companies across manufacturing, trade, and the service sector, and explains the weighting procedures used to ensure representativeness of the German economy. Additionally, it catalogs the extensive set of standard and special questions fielded since 2008 covering aspects like the COVID-19 pandemic, demographic changes, and technological transformation. The micro data is available through the LMU-ifo Economics & Business Data Center.
Keywords: C83; J20; M12; M50; 330; human resources survey; personnel management; labor market; firm behavior